2018
DOI: 10.1590/0102-311x00204016
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of chronic diseases to the prevalence of disability in basic and instrumental activities of daily living in elderly Brazilians: the National Health Survey (2013)

Abstract: This study's objective was to assess the contribution of selected chronic diseases to the prevalence of disability in elderly Brazilians, based on data from the National Health Survey (PNS 2013). Disability was defined as some degree of difficulty in performing ten activities, considering three levels: (i) without disability; (ii) disabled only in some instrumental activity of daily living (IADL); and (iii) disabled in some basic activity of daily living (BADL). The multinomial additive hazards model was the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 44 publications
(90 reference statements)
4
12
0
4
Order By: Relevance
“…Moreover, some specific illness was more related with functional dependency, according to the sex. This study confirms the association among female sex and decrease of functional capacity found in the present study 26 . Similarly to the present study, Torres et al found the females older presented more dependency for BADL and IADL, besides other factors like advanced age, have been bedridden in the last two weeks, pain in the last month, lower educational level and restrictions to leave home 27 .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, some specific illness was more related with functional dependency, according to the sex. This study confirms the association among female sex and decrease of functional capacity found in the present study 26 . Similarly to the present study, Torres et al found the females older presented more dependency for BADL and IADL, besides other factors like advanced age, have been bedridden in the last two weeks, pain in the last month, lower educational level and restrictions to leave home 27 .…”
Section: Discussionsupporting
confidence: 93%
“…[91719] In this study, ADL dependence was found to be strongly associated with chronic morbidities which highlight the importance of chronic diseases in causing disabilities in elderly. [59122223] Prevalence of ADL disability was found to be slightly higher among male in this study which is consistent with our previous report from this region. [10]…”
Section: Discussionsupporting
confidence: 91%
“…Multimorbidity is the occurrence of two or more chronic conditions in the same individual (40) , and it is associated with elements such as loss of functional capacity (39,41) , decreased grip strength (40) , frailty (42) , and cognitive impairment (43) , all of which are also associated with abuse against older adults. In addition, the literature shows that older adults with a high number of comorbidities have a higher chance of suffering violence (44) .…”
Section: Discussionmentioning
confidence: 99%